Practical Exploration of the 'Open or Close' Concept: Evaluation of the Hygrothermal Performance of a Bioclimatic Innovation for Onion Bulb Preservation - Ouedraogo, Boukaré; Bahiebo, Dieudonné Joseph; Ouedraogo, Germain; Palm, Kalifa; Kabore, Boureima (Advanced engineering forum, 2024)
Substantial losses occur during the storage of onion bulbs due to the inadequacy of available preservation technologies. In an endeavor to contribute to a solution, we evaluate the thermal efficacy of a bioclimatic innovation known as the "solar cell" for onion bulb preservation. This assessment involves recording temperature data from both external and internal walls, as well as indoor and outdoor air temperatures, solar irradiation, and relative humidity levels indoors. These measurements offer insights into crucial performance parameters such as thermal phase shift, thermal inertia, thermal decoupling between internal and external environments, relative humidity, damping factor, and thermal amplitude. Furthermore, we examine the impact of external factors, including external temperature and solar radiation. Across different facades, the thermal phase shift of the chamber's structure averages between 5.5 and 10.87 hours. Notably, the maximum thermal phase shift is observed to be 11.67 hours on the Eastern wall. The lowest recorded thermal damping factor is 0.081 on the Western wall, while the highest is 0.337 on the Northern wall. The study of thermal decoupling between the internal and external environments reveals a potential temperature differential of 13.7°C and 9.5°C during the day, and-6°C at night, contingent on the time of year. Consequently, the "close or open" operational mode proves to be of significant interest. Exposed to solar radiation peaking at 1041 W/m2, the temperatures of the external facades of the walls experience a substantial increase, reaching up to 52.3°C. Meanwhile, the internal environment maintains a thermal range of 24.21°C to 31.68°C under a maximum airflow of 0.18 m/s. The average relative humidity within the storage chamber fluctuates between 42.65% and 87%. Hence, the solar cell demonstrates its capacity to create optimal conditions of 25°C-30°C and 0.062 m/s for onion bulb conservation. Nevertheless, further enhancements are warranted for effective humidity control.